Population-based incidence of gastrointestinal stromal tumors in Puglia. Issue 1 (February 2021) - Cuccaro, Francesco; Burgio Lo Monaco, Maria Giovanna; Rashid, Ivan; Bisceglia, Lucia; Caputo, Enrico; Melcarne, Anna; Palma, Fernando; Tanzarella, Margherita; Cozzi, Emma; Coviello, Vincenzo
Introduction: This study presents the incidence of gastrointestinal stromal tumors (GISTs) in an Italian region of over 4 million inhabitants monitored for 10 years and is the largest incidence study of this type of cancer conducted so far in Italy. Methods: In order to ensure the registration of all GISTs, including those with nonmalignant behavior, a cancer list was integrated with the cases found through an ad hoc data mining process that covered all the pathologic reports of Puglia. Case distributions by sex, age groups, site, and prognostic groups according to Miettinem and Lasota classification and crude and age-standardized incidence rates were produced. Results: In the 10-year period 2006 to 2015, 708 cases of GIST were recorded in Puglia. The average crude incidence rate was 1.7 per 100, 000 person-years and the age-standardized incidence rate, using 2013 European standard population, was 1.8 per 100, 000 person-years (95% confidence interval [CI], 1.6–1.9). Incidence was higher in men than in women: crude incidence rate was 2.0 per 100, 000 person-years and age-standardized incidence rate 2.2 per 100, 000 person-years (95% CI, 2.0–2.4) in men and 1.5 per 100, 000 person-years and 1.4 per 100, 000 person-years (95% CI, 1.2–1.6) in women. Discussion: Our incidence rates are comparable with those of other international studies and they are located in the medium to high end of the range. The comparisons are affected by a different capacity of the cancer registries to intercept and record GISTs with nonmalignant behavior. Distribution of cases for sex, age groups, sites, and prognostic risk groups are consistent with previous results.